7p15 deletion as the cause of hand-foot-genital syndrome: a case report, literature review and proposal of a minimum region for this phenotype - Emiy Yokoyama (Molecular Cytogenetics, 2017)
Abstract Background Hand-foot-genital syndrome (HFGS) is a rare condition characterized by congenital malformations in the limbs and genitourinary tract. Generally, this syndrome occurs due to point mutations that cause loss of function of the HOXA13 gene, which is located on 7p15; however, there are some patients with HFGS caused by interstitial deletions in this region. Case presentation We describe a pediatric Mexican patient who came to the Medical Genetics Department at the National Institute of Pediatrics because he presented with genital, hand and feet anomalies, facial dysmorphisms, and learning difficulties. Array CGH reported a 12.7 Mb deletion that includes HOXA13. Conclusions We compared our patient with cases of HFGS reported in the literature caused by a microdeletion; we found a minimum shared region in 7p15.2. By analyzing the phenotype in these patients, we suggest that microdeletions in this region should be investigated in all patients with clinical characteristics of HFGS who also present with dysplastic ears, mainly low-set implantation with a prominent antihelix, as well as a low nasal bridge and long philtrum.